(untitled) (Research, Society and Development, 2020)
This study is part of assumption that the Environmental Education, when worked in preschool education, contributes for building new attitudes and looks about environmental care, besides forming critical beings and conscious regarding environmental degradation concerning ambient degradation accumulation of garbage disposal. The aim of this work is provide new meanings and senses with children between 4 and 5 years old, matriculated in classes of infertile IV of the Education Center Municipal for children, located in a town that belongs the north region center of Paraná State. Through field research, documentary of interviews, being it semi-structured. Got up it, analyzed it, agrouped it relevant information by study. And the end we building s trap to dengue of net with discarded objects of trash. Like results wants that the children adopt action that are careful, cooperation, solidarity and respect with environmental education where are embers.